What is a State of the Art (SotA) review? - Yu. V. Rodionova; O. T. Kim (Кардиоваскулярная терапия и профилактика)
State of the Art (SotA) literature reviews are chronological overviews of the current status of knowledge about a phenomenon and suggest directions for future research. The publication discusses the methodological principles of writing this type of review.